Assessment of esophagogastroduodenoscopy skills on simulators before real-life performance - Nielsen, Anders Bo; Pedersen, Finn Møller; Laursen, Christian B.; Konge, Lars; Laursen, Stig (Endoscopy International Open, 2022)
Background and study aims Operator competency is essential for esophagogastroduodenoscopy (EGD) quality, which makes appropriate training with a final test important. The aims of this study were to develop a test for assessing skills in performing EGD, gather validity evidence for the test, and establish a credible pass/fail score.Methods An expert panel developed a practical test using the Simbionix GI Mentor II simulator (3 D Systems) and an EGD phantom (OGI 4, CLA Medical) with a diagnostic (DP) and a technical skills part (TSP) for a prospective validation study. During the test a supervisor measured: 1) total time; 2) degree of mucosal visualization; and 3) landmarks and pathology identification. The contrasting groups standard setting method was used to establish a pass/fail score.Results We included 15 novices (N), 10 intermediates (I), and 10 experienced endoscopists (E). The internal structure was high with a Cronbach’s alpha of 0.76 for TSP time consumption and 0.74 for the identification of landmarks.Mean total times, in minutes, for the DP were N 15.7, I 11.3, and E 7.0, and for TSP., they were N 7.9, I 8.9, and E 2.9. The total numbers of identified landmarks were N 26, I 41, and E 48. Mean visualization percentages were N 80, I 71, and E 71. A pass/fail standard was established requiring identification of all landmarks and performance of the TSP in < 5 minutes. All experienced endoscopists passed, while none of the endoscopists in the other categories did.Conclusions We established a test that can distinguish between participants with different competencies. This enables an objective and evidence-based approach to assessment of competencies in EGD.